Gadolinium-doped gallic acid-zinc/aluminium-layered double hydroxide/gold theranostic nanoparticles for a bimodal magnetic resonance imaging and drug delivery system - Usman, Muhammad Sani; Hussein, Mohd Zobir; Fakurazi, Sharida; Masarudin, Mas Jaffri; Ahmad Saad, Fathinul Fikri (MDPI, 2017)
We have developed gadolinium-based theranostic nanoparticles for co-delivery of drug and magnetic resonance imaging (MRI) contrast agent using Zn/Al-layered double hydroxide as the nanocarrier platform, a naturally occurring phenolic compound, gallic acid (GA) as therapeutic agent, and Gd(NO3)3 as diagnostic agent. Gold nanoparticles (AuNPs) were grown on the system to support the contrast for MRI imaging. The nanoparticles were characterized using techniques such as Hi-TEM, XRD, ICP-ES. Kinetic release study of the GA from the nanoparticles showed about 70% of GA was released over a period of 72 h. The in vitro cell viability test for the nanoparticles showed relatively low toxicity to human cell lines (3T3) and improved toxicity on cancerous cell lines (HepG2). A preliminary contrast property test of the nanoparticles, tested on a 3 Tesla MRI machine at various concentrations of GAGZAu and water (as a reference) indicates that the nanoparticles have a promising dual diagnostic and therapeutic features to further develop a better future for clinical remedy for cancer treatment.